Effect of special exercises on blood biochemical indices of highly skilled male rowers during pre-start preparation - Vynohradov, V.; Osypenko, G.; Ilyin, V.; Vynogradova, O.; Rusanova, O. (Journal of Physical Education and Sport, 2021)
The paper presents complexes of special impacts for qualified athletes - men specializing in rowing. Reliable markers of the body's adaptation to the loads of highly qualified rowing academics are hormonal indicators in the blood serum. The influence of various complexes on the change in blood biochemical parameters in athletes - rowers is shown. Objective.Evaluating the complexes of special prelaunch exercises and mobilization massage impact in different versions of their combinations on the biochemical parameters of the blood serum of the body of highly qualified athletes -man rowers during prelaunch training. Methods of study: the study involved 6 athletes - male with qualifications of masters of sports of international class in rowing. Questionnaire surveys and biochemical blood tests were conducted before the first test of athletes (Mindray BS200 Chemistry Analyzer). Level of cortisol was determined by means of BECKMAN COULTER Access 2, whereas that of cortisol by immune-enzymatic method (MR-96A Mindray). Results. The influence of complexes of impacts on the change of athletes` hormonal status has been shown. Changes of the body biochemical reaction after each complex performance have been registered. After performing complex 1, cortisol content decreased by 26% and 7% in the first and the second athlete, respectively. The T/C index in the first athlete increased 1.4 times. After performing complex 2, cortisol content increased by 35% and 44%, whereas that of blood testosterone by 54% and 15% in the first and the second athlete, respectively;the T/C ratio before and after exposure was at the level of 0.085 and 0.098 units and 0.073 and 0.059 units in the first and the second athlete, respectively. After complex 3 execution, the athlete`s testosterone level decreased by 13%, and the change in T/C index constituted 0.072 and 0.067. After complex 4, a gradual decrease in blood cortisol by 23% was observed. Testosterone content did not change immediately after the massage, whereas by the 40th minute of rest it reduced by 21%. Conclusions.It was discovered that depending on the different complexes performed the results showed different level and directions of changes in the level of cortisol and testosterone, T/C index in blood serum of the athletes` bodies.